2018
DOI: 10.18240/ijo.2018.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the posterior corneal surface on total corneal astigmatism in patients with age-related cataract

Abstract: Posterior corneal astigmatism should be valued for more precise corneal astigmatism management, especially for higher ATR astigmatism of the anterior corneal surface. We suggest a 9% reduction in the magnitude of the simulated K in eyes with WTR astigmatism, and a 16% addition of the magnitude of the simulated K in eyes with ATR astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous studies showed that ignoring posterior corneal astigmatism may yield significant estimation errors for total corneal astigmatism in age-related cataract patients preparing for cataract surgery. To be more specific, error in magnitude was significantly increased when the magnitude of posterior corneal astigmatism was larger than 0.4 D. Additionally, when WTR anterior corneal astigmatism was more than 2.6 D or an ATR astigmatism was more than 1.6 D, the anterior measurement can cause errors influencing on the toric IOL decision [ 15 , 22 ]. In the present study, the posterior corneal astigmatism (PCA) of larger than 0.4 D, WTR anterior corneal astigmatism of larger than 2.6 D and ATR astigmatism of larger than 1.6 D accounted for 49.8, 32.2 and 23.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ignoring posterior corneal astigmatism may yield significant estimation errors for total corneal astigmatism in age-related cataract patients preparing for cataract surgery. To be more specific, error in magnitude was significantly increased when the magnitude of posterior corneal astigmatism was larger than 0.4 D. Additionally, when WTR anterior corneal astigmatism was more than 2.6 D or an ATR astigmatism was more than 1.6 D, the anterior measurement can cause errors influencing on the toric IOL decision [ 15 , 22 ]. In the present study, the posterior corneal astigmatism (PCA) of larger than 0.4 D, WTR anterior corneal astigmatism of larger than 2.6 D and ATR astigmatism of larger than 1.6 D accounted for 49.8, 32.2 and 23.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some have reported that astigmatism at the corneal posterior surface was generally less than 0.50DC. [ 18 19 20 21 22 23 24 25 26 ] It has been claimed that Orbscan II tends to overestimate characteristics of the posterior corneal surface compared with other systems. [ 5 27 ] Alternatively, it could equally be argued that other systems underestimated changes at the posterior surface of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…This might make some compensation for the binocular refractive imbalance in aniso-axial length patients. Though the contribution of the posterior corneal curvature is small [ 32 ], its effects on total corneal refractive status should not be neglected casually, especially in aniso-axial length patients.…”
Section: Discussionmentioning
confidence: 99%